Hubungan komunikasi efektif dokter-pasien terhadap tingkat kepuasan pasien dalam pelayanan medik - Dahliana Jessica Aristy Silaen; Ibnu Alferraly (DiscoverSys Inc., 2019)
Introduction: Indonesia is the biggest contributor of medical tourists to Malaysia and Singapore in recent years, mostly from Medan. Literature reviews and experts opinion of community medicine revealed that poor doctors’ communication skills in Indonesia lead to decreased patients satisfaction and lead to the number of patients seeking treatment abroad.Aim: This study aimed to analyze the relationship between physician-patient communication on the level of patient satisfaction in Central Public Hospital Haji Adam Malik, Medan.Method: This research uses a combination of descriptive-analytic study with cross sectional design. Statistical analysis was performed by chi-square test. The sample selection of research done by consecutive sampling. Measurement doctor-patient communication and patient satisfaction rate is determined by using modified CAT (Communication Assessment Tool) questionnaire.Result: Ten outpatient clinics of Central Public Hospital Haji Adam Malik (10 patients per outpatient clinic) participated in the field test. The average mean score was 4.086 across all modified CAT items (SD = 0.609, range 2.23-5.00). The average proportion of satisfaction rate was 81.7% (S.D. = 12.19, range 44.62-100%). There was a significant relationship between physician-patient communication with patient satisfaction (p <0.05).Conclusion: Assessment doctor-patient communication in Outpatient Clinics of Central Public Hospital Haji Adam Malik categorized as good. Patient satisfaction rate in Outpatient Clinics of Central Public Hospital Haji Adam Malik categorized as satisfied. Effective physician-patient communication associated with patient satisfaction with the physician.